FRI0335 The Eurofever Project: Towards the Longitudinal Stage. (9th June 2015) - Federici, S.; Frenkel, J.; Ozen, S.; Finetti, M.; Garibotto, F.; Lachmann, H.; Martini, A.; Ruperto, N.; Gattorno, M.
Abstract : Background: In 2008 the Paediatric Rheumathology European Society (PReS) promoted an International Project (EAHC, Project No2007332) for the study of Autoinflammatory Diseases (AIDs) named Eurofever whose main purpose is to create a web-based registry for the collection of clinical, laboratory and response to treatment information in patients with AIDs. Objectives: To implement the Registry with the new recently described AIDs and genes and modify the web-system to make it suitable for the collection of longitudinal data and for a better collection of data regarding treatment. Methods: With the technical help of Paediatric Rheumatology INternational Trial Organization (PRINTO) web-masters, we were able to revise the electronic case report forms bringing 2 main novelties: i) inclusion of the more recently described AIDs (DADA2, CAMPS, SAVI) and the relative clinical manifestation ii) modification of drug layout for a better collection of data regarding treatment. In this process information on safety and efficacy have been included. Very soon Centres will be asked to update on a yearly base the information regarding each patient with particular focus on modification of the clinical picture, onset of complication/sequelae, treatment, adverse event if present, laboratory and instrumental findings. Results: Up to date 3089 patients have been enrolled in the Registry from 101 centers in 38 countries. At present baseline demographic information from 3089 (M:F=1513:1576) patients are available. In 77% complete clinical information from disease onset to diagnosis and response to treatment is also available. For each disease the number of enrolled patients is: FMF 894 pts (708 with complete clinical data); TRAPS 268 pts (226 complete); CAPS 284 pts (208 complete); MKD 189 pts (165 complete); Blau's disease 71 pts (22 complete); PAPA 27 pts (22 complete); NLRP-12 mediated periodic fever 14 pts (9 complete); DIRA 3 pts (all complete); CANDLE 2 pts (1 complete), Schnitzler 1 pt and Majeed 2 pts (both complete). Among multifactorial autoinflammatory diseases: PFAPA 612 pts (380 complete); CRMO 417 pts (394 complete); pediatric Bechet disease 92 pts (72 complete) and 217 patients with undefined periodic fever (182 complete). Longitudinal electronic data capture is now ready and online for authorized PRINTO members. The enrollment for the longitudinal part will start on February 2015. Conclusions: A common registry for collection of patients with Autoinflammatory disease is available and the enrolment is ongoing. This project represent the first attempt of a common registry for different Autoinflammatory Syndromes. The longitudinal collection and analysis of data coming from the Registry will improve our knowledge in the field of Autoinflammation both on the natural history of the single disease and the efficacy and safety of the treatment commonly used in the clinical practice with particular regards to biologics. Disclosure of Interest: None declared